Intrauterine ultrasound phenotyping, molecular characteristics, and postnatal follow-up of fetuses with the 15q11.2 BP1-BP2 microdeletion syndrome: a single-center, retrospective clinical study - Meiying Cai; Aixiang Lv; Wantong Zhao; Liangpu Xu; Na Lin; Hailong Huang (BMC, 2024)
Abstract Objectives The 15q11.2 BP1-BP2 microdeletion is associated with neurodevelopmental diseases. However, most studies on this microdeletion have focused on adults and children. Thus, in this study, we summarized the molecular characteristics of fetuses with the 15q11.2 BP1-BP2 microdeletion and their postnatal follow-up to guide prenatal diagnosis. Methods Ten thousand fetuses were retrospectively subjected to karyotype analysis and chromosome microarray analysis. Results Chromosome microarray analysis revealed that 37 (0.4%) of the 10,000 fetuses had 15q11.2 BP1-BP2 microdeletions. The fragment size of the 15q11.2 BP1-BP2 region was approximately 312-855 kb and encompassed TUBGCP5, CYFIP1, NIPA2, and NIPA1 genes. Twenty-five of the 37 fetuses with this microdeletion showed phenotypic abnormalities. The most common ultrasonic structural abnormality was congenital heart disease, followed by renal dysplasia and Dandy-Walker malformation. The 15q11.2 BP1-BP2 microdeletion was inherited from the father and mother in 6 and 10 cases, respectively, and de novo inherited in 4 cases. In the postnatal follow-up, 16.1% of the children had postnatal abnormalities. Conclusion Fetuses with the 15q11.2 BP1-BP2 microdeletion showed high proportions of phenotypic abnormalities, but the specificity of penetrance was low. Thus, fetuses with this syndrome are potentially at a higher risk of postnatal growth/behavioral problems and require continuous monitoring of growth and development.